2013
DOI: 10.25011/cim.v36i4.19951
|View full text |Cite
|
Sign up to set email alerts
|

A unifying framework for depression: Bridging the major biological and psychosocial theories through stress

Abstract: A unifying framework for depression: Bridging the major biological and psychosocial theories through stress AbstractSeveral mechanisms for the development of depression have been proposed, and a comparative examination reveals considerable overlap. is paper begins by summarizing the conclusions drawn in the literature on the major biological theories: HPA-axis hyperactivity, the monoamine theory, the cytokine hypothesis/ macrophage theory, and structural changes to relevant brain regions and neurons. It then d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 171 publications
0
39
0
Order By: Relevance
“…Epidemiological studies have clearly shown that chronic psychological stressors are critical contributors to the development of depression in humans (Björkqvist, 2001;Meltzer et al, 2011;Roy and Campbell, 2013;Taylor et al, 2011). Such repeated exposure to a social stressor can be mimicked in rodents by using a modified version of the resident-intruder procedure called social defeat, which generates persistent emotional stress (Tidey and Miczek, 1997).…”
Section: Nucleus Accumbensmentioning
confidence: 99%
“…Epidemiological studies have clearly shown that chronic psychological stressors are critical contributors to the development of depression in humans (Björkqvist, 2001;Meltzer et al, 2011;Roy and Campbell, 2013;Taylor et al, 2011). Such repeated exposure to a social stressor can be mimicked in rodents by using a modified version of the resident-intruder procedure called social defeat, which generates persistent emotional stress (Tidey and Miczek, 1997).…”
Section: Nucleus Accumbensmentioning
confidence: 99%
“…Since there is also a strong causal association between chronic stress and depression (Hammen, 2005), the obvious pathway runs from poverty to stress, and then to risk of depression. Roy and Campbell (2013) provide an introduction to the biology of the poverty-stress-depression feedback mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Other structures in the limbic system (e.g. the hypothalamus, amygdala and hippocampus) have also been associated with depression (Drevets, 2000;Roy & Campbell, 2013).…”
Section: Neurotransmitter and Antidepressant Models Of Depression Thmentioning
confidence: 99%
“…Reduced hippocampal volume has consistently been linked to depression and is thought be a consequence of recurrent episodes of depression (Videbech & Ravnkilde, 2004). The importance of the hippocampus in understanding the pathophysiology of depression is also supported by the presence of the monoaminergic and glutamatergic systems in the hippocampus, which are networks of neurons involved in antidepressant action and response (see 1.6.5.1 Neurotransmitter and antidepressant models of depression) (Roy & Campbell, 2013). It is not clear whether structural alterations in depression are a state effect, which are reversible, or if they predate the onset of depression and worsen over time (Palazidou, 2012).…”
Section: Neurotransmitter and Antidepressant Models Of Depression Thmentioning
confidence: 99%
See 1 more Smart Citation